Acute Limb Ischaemia during ECMO Support: A 6-Year Experience - Ihor Krasivskyi; Clara Großmann; Marit Dechow; Ilija Djordjevic; Borko Ivanov; Stephen Gerfer; Walid Bennour; Elmar Kuhn; Anton Sabashnikov; Parwis Baradaran Rahmanian; Navid Mader; Kaveh Eghbalzadeh; et al. (Life, 2023)
The use of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) for cardiogenic shock is rising. Acute limb ischaemia remains one of the main complications after ECMO initiation. We analysed 104 patients from our databank from January 2015 to December 2021 who were supported with mobile ECMO therapy. We aimed to identify the impact of acute limb ischaemia on short-term outcomes in patients placed on ECMO in our institution. The main indication for ECMO therapy was left ventricular (LV) failure with cardiogenic shock (57.7%). Diameters of arterial cannulas (p = 0.365) showed no significant differences between both groups. Furthermore, concomitant intra-aortic balloon pump (IABP, p = 0.589) and Impella (p = 0.385) implantation did not differ significantly between both groups. Distal leg perfusion was established in approximately 70% of patients in two groups with no statistically significant difference (p = 0.960). Acute limb ischaemia occurred in 18.3% of cases (n = 19). In-hospital mortality was not significantly different (p = 0.799) in both groups. However, the bleeding rate was significantly higher (p = 0.005) in the limb ischaemia group compared to the no-limb ischaemia group. Therefore, early diagnosis and prevention of acute limb ischaemia might decrease haemorrhage complications in patients during ECMO therapy.